Fluorescence detection of malachite green and cations (Cr3+, Fe3+ and Cu2+) by a europium-based coordination polymer. Issue 14 (17th March 2022) - Kong, Ya-Jie; Hou, Guo-Zheng; Gong, Zhao-Ning; Zhao, Feng-Tan; Han, Li-Juan
Abstract : A europium-based CP fluorescent sensor was synthesized and exhibited excellent recognition ability for malachite green (MG) and metal cations (Cr 3+, Fe 3+ and Cu 2+ ). Abstract : Due to remarkable fluorescence characteristics, lanthanide coordination polymers (CP) have been widely employed in fluorescence detection, but it is rarely reported that they act as multifunctional luminescent probes dedicated to detecting malachite green (MG) and various metal ions. A europium-based CP fluorescent probe, Eu(PDCA)2 (H2 O)6 (PDCA = 2, 6-pyridinedicarboxylic acid), has been synthesized and exhibited excellent recognition ability for malachite green and metal cations (Cr 3+, Fe 3+ and Cu 2+ ) among 11 metal cations, 13 anions and six other compounds. The recognition was achieved by fluorescence quenching when MG, Cr 3+, Fe 3+ and Cu 2+ were added to a suspension of Eu(PDCA)2 (H2 O)6 respectively. Eu(PDCA)2 (H2 O)6 is a multifunctional luminescent probe, and displayed high quenching efficiencies K sv (2.10 × 10 6 M −1 for MG; 1.46 × 10 5 M −1 for Cr 3+ ; 7.26 × 10 5 M −1 for Fe 3+ ; 3.64 × 10 5 M −1 for Cu 2+ ), and low detection limits (MG: 0.039 μM; Cr 3+ : 0.539 μM; Fe 3+ : 0.490 μM; Cu 2+ : 0.654 μM), presenting excellent selectivity and sensitivity, especially for MG. In addition, Eu(PDCA)2 (H2 O)6 was also made into fluorescent test strips, which can rapidly and effectively examine trace amounts of MG, Cr 3+, Fe 3+ and Cu 2+ in aqueous solutions. This work provides a new perspective for detecting malachite green in fish ponds and heavy metal ions in waste water.